PENGARUH PENERAPAN TEKNIK DUA TINGGAL DUA TAMU DISERTAI SPEED TEST TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Irawan, Benni; Rahmi, Rahmi; Febriana, Rina (STKIP PGRI Sumbar, 2013)
The research was motivated by the students comprehension of mathematical concept at eighth grade students of SMPN 1 Lembah Melintang is still low. It is caused by the learning process still focuses on the teachers and group learning is not maximized. This research aims to 1). Determine how the development of students comprehension of mathematical concept in the experimental class, 2). Determine whether students comprehension of mathematical concept by using technique of Two Stay Two Stray with Speed Test was better than students comprehension of mathematical concept that apply conventional learning at eighth grade students of SMPN 1 Lembah Melintang. Type of this research is experimental research by using randomized control group only design. Based on the value of speed test students comprehension of mathematical concept was increased at each meeting and the results of the data analysis obtained from the average of results of studentâ learning in the experimental class was 69.35 higher than the control class was 58.97. It can be concluded that students comprehension of mathematical concept by applying technique of Two Stay Two Stray was better than students comprehension of mathematical concept that apply conventional learning.